PENGARUH PENGETAHUAN, RELIGIUSITAS, DAN KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH PADA BANK SUMSEL BABEL SYARIAH KCP UIN RADEN FATAH PALEMBANG - Abubakar Sidik; Riska Nuari; Disfa Lidian Handayani (Journal of Economics and Business, 2023)
This study aims to analyze or find out how the influence of Knowledge, Religiosity and Service Quality on Customer Loyalty of Bank Sumsel Babel Syariah KCP Uin Raden Fatah Palembang. This study uses quantitative methods and uses primary data by distributing questionnaires to 100 respondents. Furthermore, analysis was carried out with the validity test, reliability test, classical assumption test, multiple linear regression analysis and hypothesis testing using the T test and F test. Processed using the SPSS Version 26 program. The research results show that the knowledge variable has a positive and significant effect on Customer Loyalty. The Religiosity variable has a positive and significant effect on Customer Loyalty. The Service Quality variable has a positive and significant effect on Customer Loyalty. So it is obtained that all variables simultaneously have a positive and significant effect.